INDICATORS OF THE USE OF ECONOMIC CRITERIA FOR IMPROVING THE QUALITY OF EDUCATION - Ibragimova Gulnoza Sayidmurodovna (Journals Park Publishing, 2024)
The article will discuss what is a problem with improving the quality of education and how to eliminate them. This will examine the mistakes that have been made in education. Prevention of factors affecting the quality of education will be discussed.
Keywords: Education, standard of education, pedagogical technology, educational activities, integrated system.